2021
DOI: 10.3390/plants10112547
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Nutrient Management Enhances Productivity and Nitrogen Use Efficiency of Crops in Acidic and Charland Soils

Abstract: Integrated Plant Nutrient System (IPNS) is practiced worldwide to maintain soil quality. Two field experiments were conducted in 2019 and 2020 in acidic and charland soils to assess the impact of different manures, viz., poultry manure (PM), vermicompost (VC), compost (OF), rice husk biochar (RHB), poultry manure biochar (PMB)-based IPNS, and dolomite over control on productivity and nitrogen use efficiency (NUE) of the Mustard-Boro-Transplanted Aman and Maize-Jute-Transplanted Aman cropping patterns, and on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…According to Salahin et al [ 24 ], it was found that the combination of inorganic and organic compounds yielded better results in terms of rice equivalent production compared to various doses of chemical fertilizers. Rahman et al [ 60 ] also stated that both organic and inorganic fertilizers enhance the productivity of the mustard-boro-T. aman rice and maize-jute-T. aman rice cropping system. Furthermore, Islam et al [ 20 ] observed that a cropping system based on four crops exhibited higher production efficiency compared to a cropping system based on three crops.…”
Section: Resultsmentioning
confidence: 99%
“…According to Salahin et al [ 24 ], it was found that the combination of inorganic and organic compounds yielded better results in terms of rice equivalent production compared to various doses of chemical fertilizers. Rahman et al [ 60 ] also stated that both organic and inorganic fertilizers enhance the productivity of the mustard-boro-T. aman rice and maize-jute-T. aman rice cropping system. Furthermore, Islam et al [ 20 ] observed that a cropping system based on four crops exhibited higher production efficiency compared to a cropping system based on three crops.…”
Section: Resultsmentioning
confidence: 99%
“…In Indonesia, the use of composted oyster mushroom baglog waste at 15 tha −1 integrated with chemical fertilizers (urea, super phosphate, and potassium chloride) in ASS supplied N, P, and K in available forms and reduced the amount of soluble Al and Fe [68]. In Bangladesh, INM involving poultry manure biochar (PMB) and dolomite increased the system productivity of Mustard-Boro-transplanted Aman and Maize-Jute-transplanted Aman cropping systems from 55.4 to 82.8% in acidic soil [110]. The composition and chemical properties of PMB used in the above study were organic carbon (337.6 g kg −1 ), total nitrogen (30.8 g kg −1 ), pH (8.5), CEC (35.68 cmolc kg −1 ), available P (1437 mg kg −1 ), available K (22.61 cmolc kg −1 ), and available S (2094 mg kg −1 ).…”
Section: Integrated Nutrient Managementmentioning
confidence: 99%
“…Green manuring involves in situ ploughing under and the incorporation of undecomposed green plants, particularly legumes, such as Dhaincha (Sesbania sp. ), Sunnhemp (Crotalaria juncea), etc., for the purpose of improving soil fertility, productivity, and physical conditions [110]. This increases soil fertility by the addition of organic matter (OM) as well as nitrogen [118].…”
Section: Green/organic Manuring and Mulchingmentioning
confidence: 99%
“…Acidic and charland soils currently constitute a major problem in soils comprising about 7.52 Mha of land and seriously affecting crop production in more than 36% of the territory in Bangladesh (Satter and Islam, 2010;FRG, 2018;Islam et al, 2021a;Uddin et al, 2021). Acidic soils have only small amounts of organic matter, low macronutrient availability, and micronutrient toxicity, thereby contributing to poor soil fertility (Kumar et al, 2019;Islam et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Acidic soils have only small amounts of organic matter, low macronutrient availability, and micronutrient toxicity, thereby contributing to poor soil fertility (Kumar et al, 2019;Islam et al, 2021b). The poor fertility of charland soils is due to their coarse texture, low soil organic carbon (SOC) concentration, macronutrient content, and soil moisture retention capability (Ali et al, 2020;Rahman et al, 2021). Continuous and unchecked use of synthetic chemical fertilizers in these soils causes acute nutrient deficiencies and impairs soil physicochemical characteristics by increasing soil acidity, resulting in rapid degradation of soil health, productivity, stability, and sustainability (Selim and Al-Owied, 2017;Selim, 2018).…”
Section: Introductionmentioning
confidence: 99%